Recent Advances in Wheat Bran Polysaccharides: Extraction, Structure and Bioactivities - Songye SHI; Jiping WEN; Yuanxiao LIU (Shipin gongye ke-ji, 2023)
Wheat bran is a by-product of wheat processing, which contains many nutrients, such as protein, vitamins, dietary fiber, phenols and polysaccharides. Studies have shown that wheat bran polysaccharide can prevent diabetes, lower blood sugar, improve immunity, anti-tumor and other effect. It has broad development prospects in daily necessities, health food and medical supplies. Different extraction and purification methods of wheat bran polysaccharides will cause differences in the structure of wheat bran polysaccharides, but the structure affects its biological activity. Therefore, it is of great significance to explore the structural characteristics of wheat bran polysaccharide to reveal its biological activity. In this paper, the extraction method, separation and purification, structure characterization and physiological function of wheat bran polysaccharide in recent years are described. At the same time, the structure-activity relationship between the structure of wheat bran polysaccharide and its biological activities is discussed. The present problems and application prospect of wheat bran polysaccharide are prospected in order to provide theoretical basis and new ideas for the utilization and research of wheat bran polysaccharide in health care and medicine.